Storage Capacity of some Temperate Shrubs - Bhagat, Sarjan; Singh, Virendra (Indian Forester, 1994)
The results of the longevity tests of Dodonaea viscosa, Indigofera gerardiana and Rubus ellipticus revealed that acid scarified seeds of these species stored in paper bags (100 gauge) and closed glass bottles at normal room temperature retained good viability upto 11,17 and 6 months. Similarly, Coriaria nepalensis, Berberis aristata and Debregeasia hypoleuca seeds stored in closed glass bottles at ambient room conditions appeared to have good storing ability exhibiting good viability upto 14 and 24 months.